The Power of Forward Guidance in NEMO - Drago Bergholt; Sara S. Meyer; Yasin Mimir; Øistein Røisland (Norges Bank, 2019)
This staff memo revisits the power of forward guidance with particular emphasis on the effectiveness of anticipated policy in Norges Bank's main policy model NEMO. First we explain, within the context of a simple toy model, why and how forward guidance has implausible effects in standard monetary policy frameworks. Second, we discuss some of the main solutions to the so-called forward guidance puzzle. We argue that existing proposals, including effective discounting as in Gabaix (2018), come with serious limitations once guidance about nominal policy rates is considered. With these lessons in mind, we proceed with a quantitative assessment of forward guidance in NEMO. It is shown that the presence of several real and nominal frictions reduces the net effects of forward guidance compared with the simple model. A powerful expectations channel is still at play: agents in NEMO believe that expansionary interest rate paths will be counteracted at some point in the future, resulting in limited net effects of forward guidance policies. We briefly discuss the realism of this feature.
hdl:11250/2601171
Keywords: 330